PENGARUH MEDIA VIDEO ANIMASI LALU LINTAS TERHADAP PERILAKU DISIPLIN BERLALU LINTAS ANAK USIA 5-6 TAHUN - Lestari, Wici; Suningsih, Taruni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Disciplined behavior reflects an attitude of obedience, orderliness, and regularity that is formed through the learning process and the influence of the individual's environment. Basically, behavior is a human action that can be observed through interaction with the environment. This study aims to determine the effect of animated traffic video media on traffic discipline behavior in children aged 5-6 years. This research method uses a pre-experimental with a one-shot case study design. The research sample consisted of 15 children aged 5-6 years. Data were collected through observation using checklist sheets, oral tests, and documentation. The results of the t-test statistical analysis showed a value of 5.35 compared to the t-table value of 1.761, which means that there is a significant effect of the use of animated traffic video media on children's traffic discipline behavior at Az-Zahrah Islamic Kindergarten, Palembang. After the application, the children were able to watch the video until the end, not make a fuss, wait their turn when asked by the teacher, know the regularity of traffic, cross at the zebra crossing, and look right and left before crossing the road.